Interferon receptor-deficient mice are susceptible to eschar-associated rickettsiosis - Thomas P Burke (eLife Sciences Publications Ltd, 2021)
Arthropod-borne rickettsial pathogens cause mild and severe human disease worldwide. The tick-borne pathogen Rickettsia parkeri elicits skin lesions (eschars) and disseminated disease in humans; however, inbred mice are generally resistant to infection. We report that intradermal infection of mice lacking both interferon receptors (Ifnar1-/-;Ifngr1-/-) with as few as 10 R. parkeri elicits eschar formation and disseminated, lethal disease. Similar to human infection, eschars exhibited necrosis and inflammation, with bacteria primarily found in leukocytes. Using this model, we find that the actin-based motility factor Sca2 is required for dissemination from the skin to internal organs, and the outer membrane protein OmpB contributes to eschar formation. Immunizing Ifnar1-/-;Ifngr1-/- mice with sca2 and ompB mutant R. parkeri protects against rechallenge, revealing live-attenuated vaccine candidates. Thus, Ifnar1-/-;Ifngr1-/- mice are a tractable model to investigate rickettsiosis, virulence factors, and immunity. Our results further suggest that discrepancies between mouse and human susceptibility may be due to differences in interferon signaling.